2015
DOI: 10.18632/oncotarget.3930
|View full text |Cite
|
Sign up to set email alerts
|

CUEDC2 down-regulation is associated with tumor growth and poor prognosis in lung adenocarcinoma

Abstract: CUE domain-containing 2 (CUEDC2) is a multi-functional protein, which regulates cell cycle, growth factor signaling and inflammation. We found that CUEDC2 was low in lung adenocarcinoma cell lines and lung adenocarcinoma tissues at both mRNA and protein levels. Low levels of CUEDC2 were correlated with a shorter survival time in patients with lung adenocarcinoma (p = 0.004). CUEDC2 expression was correlated with tumor T classification (P = 0.001) at clinical stage (P = 0.001) and tumor size (P = 0.033). Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The results of the present study are supported by results of a previous study where overexpression of CUEDC2 was considered a predictor of poor prognosis of ovarian serous carcinoma ( 42 ). However, a recent study reported that CUEDC2 knockdown could increase tumor growth in lung adenocarcinoma ( 43 ). It has therefore been suggested that the function of CUEDC2 may be dependent on cell type.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are supported by results of a previous study where overexpression of CUEDC2 was considered a predictor of poor prognosis of ovarian serous carcinoma ( 42 ). However, a recent study reported that CUEDC2 knockdown could increase tumor growth in lung adenocarcinoma ( 43 ). It has therefore been suggested that the function of CUEDC2 may be dependent on cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described [22, 23]. Briefly, cells were lysed in radio-immunoprecipitation buffer, and clarified lysates were resolved by SDS-PAGE and transferred onto polyvinylidene fluoride membranes (Millipore, Bedford, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described. 30 , 31 In brief, tissues and cells were lysed in RIPA buffer (Beyotime, Haimen, People’s Republic of China), and after centrifugation at 13,000 g for 15 min, the concentration of protein in the supernatant was measured using BCA kit (Pierce, Waltham, MA, USA). Approximately 50 μg protein was resolved by 10% SDS-PAGE and transferred onto PVDF membranes (EMD Millipore, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%